PENGEMBANGAN MOBILE LEARNING UNTUK MATA KULIAH JARINGAN KOMPUTER BERBASIS ANDROID - Fatsyahrina Fitriastuti; Yumarlin Yumarlin MZ (Universitas Janabadra, 2017)
ABSTRACTThis study aims to design interactive multimedia for computer network courses with Android-based so that it can be accessed via smartphone. Computer Network course is one of compulsory subjects in Informatics Engineering course. With the realization of multimedia is expected to shorten the learning time of students, and students can more easily understand the material of computer networks rather than through the tutorial tutorial as usual, and is expected to improve learning achievement. This multimedia realization chose to use the Android operating system to be accessible memlaui smartphone that is currently widely used by the students. This interactive multimedia presents theories, simulations and problems as the evaluation of computer network learning. The results of this interactive multimedia will be tested through the test instrument to the students on the study program of Inormatika Technique of Janabadra University. Instrument test used to know student achievement. Test instrument used is a questionnaire instrument to determine the quality of interactive multimedia computer network courses. Multimedia is designed using the main software such as Macromedia Flash, Macromedia Director, and Macromedia Authorware and Eclipse 4.2 along with supporting applications. The material to be delivered on interactive multimedia is tailored to the syllabus of computer network courses on Strata 1 level. The expected research output is in the form of teaching materials for the enrichment of computer network subjects and multimedia technology and will be socialized through the national seminar in the field of informatics engineering. Keywords: interactive multimedia, Android, computer network